Ensino de geografia e ENEM : cidadania, resultados e um compromisso com a educação geográfica - Lopes, Fernanda Brum (2024)
The general objective of this work is to identify the way in which Geography is approached in the National High School Exam and its relationship with the geographic content practiced in the classroom. The methodological procedure used was through documentary-bibliographical research and content analysis, which sought to identify the geographic interdisciplinarity in Enem, based on checking questions from the Enem tests, referring to the years 2017-2020, of the first printed application. A survey of the microdata provided by Inep was carried out. A qualitative approach was used to collect and process data. The identification of the Enem items revealed that geographic knowledge is present in all areas of knowledge (Languages, Humanities, Nature and Mathematics) as Geography allows the student to understand the world in its various scales and dimensions - economic, political , cultural, environmental, social, natural – and the understanding that it is in man's action on the natural environment that geographic space is constantly (re)constructed with different purposes and intentions, making it a science of relationships. Among this evidence, we seek to reflect on how to work with Geography in the classroom that allows good results in Enem and the development of citizenship? It was found that Geography in Enem is the Geography we practice in the classroom, but, above all, for the teacher to practice Geography without the anxiety of assessments, Geography in Enem must be Geographic Education, which has as The central point is education for life, making it possible to achieve results and providing resources to reflect on one's place in the world and guarantee citizenship.